Каджарский библиофил Бахман Мирза и его молитвенник «Зад-ул-Ми’ад» из коллекции Матенадарана - Амирбекян, Раиса («Նաիրի» հրատ.)
Մատենադարանի թանգարանային համալիրի ցուցադրություններից մեկը արաբատառ ձեռագրերի դահլիճն է, որի զարդերից է նրբաճաշակ մի ձեռագիր՝ իսլամական աղոթքների «Զադ-ուլ Մի’ադ» վերնագրով ժողովածուն (XIX դարի կեսեր): Այն ընդօրինակվել է Թավրիզում՝ գեղագիր Մուհամմադ Ալի իբն Մուհամմադ Շաֆի Թաբրիզիի ձեռքով: Աղոթագիրգքն ունի վերնագիր, պատվիրատուի և կատարողի անունները, ընդօրինակման վայրն ու ժամանակը: Նրան հատուկ է գեղարվեստական բարձր մակարդակ: Հնարավոր է նկատել նաև գրքի տեղաշարժման բավականին ճշգրիտ հետագիծը: One of the permanent exhibitions at the Matenadaran museum complex, the hall of Arabic-Script manuscripts, houses a treasure: an exquisite mid-19th century manuscript entitled Zad-ul Mi’ad. It is a well-known Islamic collection of prayers by Muhammad Bakir, copied in Tabriz by calligrapher Muhammad ‘Ali ibn Muhammad Shafi Tabrizi. The manuscript contains references to the place and time of its copying, the names of the commissioner and the scribe. It is also possible to trace, quite clearly, how the book has been carried from place to place. The manuscript is of great artistic value.
Keywords: Искусство; Молитвенники; Коллекции Матенадарана